Handbook of Social Network Technologies and Applications - Furht, Borko; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Social networking is a concept that has existed for a long time; however, with the explosion of the Internet, social networking has become a tool for people to connect and communicate in ways that were impossible in the past. The recent development of Web 2.0 has provided many new applications, such as Myspace, Facebook, and LinkedIn. Handbook of Social Network Technologies and Applications provides comprehensive guidelines on the current and future trends in social network technologies and applications in the field of Web-based Social Networks. Contributed by world experts in the field of social networks from both academia and private industry, a number of crucial topics are covered including cutting edge social network technologies, infrastructures, and communities; social media analysis, organizations, mining, and search; privacy and security issues in social networks; and visualization and applications of social networks. Topics presented include: Perspectives on Social Network Analysis for Observational Scientific Data Discovering Mobile Social Networks by Semantic Technologies Online Identities and Social Networking Decentralized Online Social Networks Accessibility Testing of Social Websites Understanding and Predicting Human Behavior for Social Communities Security and Privacy Threats in Online Social Networks Online Advertising in Social Networks Handbook of Social Network Technologies and Applications provides a definitive resource for a wide variety of people including academicians, designers, developers, educators, engineers, practitioners, researchers, and graduate students. This book is also beneficial for business managers, entrepreneurs, and investors.
SOCIAL MEDIA ANALYSIS AND ORGANIZATION -- Social Network Analysis: History, Concepts, and Research -- Structure and Dynamics of Social Networks Revealed by Data Analysis of Actual Communication Services -- Analysis of Social Networks by Tensor Decomposition -- Analyzing the Dynamics of Communication in Online Social Networks -- Qualitative Analysis of Commercial Social Network Profiles -- Analysis of Social Networks Extracted from Log Files -- Perspectives on Social Network Analysis for Observational Scientific Data -- Modeling Temporal Variation in Social Network: An Evolutionary Web Graph Approach -- Churn in Social Networks -- SOCIAL MEDIA MINING AND SEARCH -- Discovering Mobile Social Networks by Semantic Technologies -- Online Identities and Social Networking -- Detecting Communities in Social Networks -- Concept Discovery in Youtube.com Using Factorization Method -- Mining Regional Representative Photos from Consumer-Generated Geotagged Photos -- Collaborative Filtering Based on Choosing a Different Number of Neighbors for Each User -- Discovering Communities from Social Networks: Methodologies and Applications -- SOCIAL NETWORK INFRASTRUCTURES AND COMMUNITIES -- Decentralized Online Social Networks -- Multi-Relational Characterization of Dynamic Social Network Communities -- Accessibility Testing of Social Websites -- Understanding and Predicting Human Behavior for Social Communities -- Associating Human-Centered Concepts with Social Networks Using Fuzzy Sets -- PRIVACY IN ONLINE SOCIAL NETWORKS -- Managing Trust in Online Social Networks -- Security and Privacy in Online Social Networks -- Investigation of Key-Player Problem in Terrorist Networks Using Bayes Conditional Probability -- Optimizing Targeting of Intrusion Detection Systems in Social Networks -- Security Requirements for Social Networks in Web 2.0 -- VISUALISATION AND APPLICATIONS OF SOCIAL NETWORKS -- Visualization of Social Networks -- Novel Visualizations and Interactions for Social Networks Exploration -- Applications of Social Network Analysis -- Online Advertising in Social Networks -- Social Bookmarking on a Company$1 (Bs Intranet: A Study of Technology Adoption and Diffusion.s
Keywords: Computer science; Computer network architectures; Information systems; Multimedia systems; Social sciences -- Data processing; Information Systems; Computer Science; Management of Computing and Information Systems; Information Systems Applications (incl.Internet).; Computer Systems Organization and Communication Networks; Multimedia Information Systems; Computer Appl. in Social and Behavioral Sciences